Iatrogenic metacarpal fracture after K-wire fixation: A case report and prevention. (2019) - Gu, Ja Hea; Choi, Su Hyun
Highlights: There are possibility of iatragenic fracture anywhere K-wire have passed and failed. Surgeons should be aware of the potential damage to bone during K-wire fixation. Preoperative planning, continuous C-arm scanning and appropriate K-wire thickness can minimize complications. Patients should be told that following K-wire removal, the residual holes could subject to stress risers. Abstract: Introduction: Iatrogenic fractures after failed K-wire fixation in the management of a carpometacarpal (CMC) joint fracture-dislocation have not yet been reported (Hsu et al., 2011). We present a case of K-wire-related complication in the management of a CMC joint fracture-dislocation and highlight the importance of planning K-wire placement and minimizing the number of K-wire passes. Presentation of case: After beating his hand against a wall, a 22-year-old patient visited our clinic complaining of a swollen and painful wrist. Following our protocol, reduction and K-wire fixation was planned. During these procedures, the resident of our team made several attempts to insert transfixation pins and radiologic finding demonstrated incorrect placement of the K-wire track. The patient visited the outpatient clinic at 5 weeks postoperatively then we removed the K-wires and began mobilization. Two weeks later, the patient came back with acute onset of pain and swelling at the 5th metacarpal area. Discussion: Stahl and Schwartz reported that 27.8 % of complications related K-wire were due to technical failure and 90 % of technical failure were caused by hospital residents. Well-established guidelines and supervision by a highly experienced surgeon is likely to reduce the rate of technical failure. Multiple passes of the K-wire have resulted in blunting of the K-wire and subsequent heat generation then lead to subsequent loosening and loss of fixation. Conclusion: Preoperative planning, marking the K-wire route, and appropriate K-wire thickness minimize such complications. Patients should be informed that following K-wire removal, the residual holes could be subject to stress risers.